Avoiding evolutionary inefficiencies in innovation networks - Andreas Pyka (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2011)
Innovation policy is in need for a rational which allows the design and evaluation of policy instruments. In economic policy traditionally the focus is on market failures and efficiency measures are used to decide whether policy should intervene and which instrument should be applied. In innovation policy this rational cannot meaningfully be applied because of the uncertain and open character of innovation processes. Uncertainty is not a market failure and cannot be repaired. Inevitably policy makers are subject to failure and their goals are to be considered as much more modest compared to the achievement of a social optimum. Instead of optimal innovation, the avoidance of evolutionary inefficiencies becomes the centrepiece of innovation policy making. Superimposed to the several sources of evolutionary inefficiencies are socalled network inefficiencies. Because of the widespread organisation of innovation in innovation networks, the network structures and dynamics give useful hints for innovation policy, where and when to intervene.
urn:nbn:de:bsz:100-opus-6540
Keywords: 330; innovation policy; innovation networks; uncertainty; exploration and exploitation; evolutionary inefficiencies; policy rational